Banana Diversity E-module for Contextual Learning in High School Education - Dwi Ratnasari; Esi Sohipah; Novi Ramadani Pratiwi; Nani Maryani (Journal of Pedagogy and Education Science, 2026)
This research aims to develop an e-module with banana diversity in Serang City, Banten, as its content to be used as an alternative learning resource for high school students. The research method used is the research and development (R&D) method. Data on various banana types in Serang were systematically collected and identified through surveys conducted across both traditional and modern markets. The resulting e-module underwent rigorous validation diversity and education technology experts, achieving high feasibility scores of 96.67% and 88.55%, both values classified as a very decent category. Subsequently, a limited trial was conducted with 32 tenth-grade science students at SMAN 8 Serang, where the e-module was used to teach the biodiversity topic. Student responses analysis yielded a score of 82.1%, which falls in the appropriate category. Overall, this study successfully provided a contextual learning medium that utilizes local biodiversity as relevant content, proving the e-module’s utility in high school biology classes. Moreover, the e-module is particularly suitable for showcasing local biodiversity, thereby enriching students’ understanding of Indonesian biodiversity as a whole. E-module can change the way students learn about biodiversity to be more relevant, interactive, and based on local potential.